Cartografando Práticas Pedagógicas de Educadores/as da Educação Infantil de Lavras-MG: o deságue das artes a partir do 145º Fórum Sul Mineiro de Educação Infantil - Buscácio, Alana Máximo (2021)
In this research has as objective to map the training process of educators (men/women) in the municipality of Lavras–MG. From the context of the 145th Forum of Early Childhood Education from South of Minas Gerais, whose theme was “Art in the Reference Curriculum of Minas Gerais: transforming realities in possibilities”.The work is justified by the importance of problematizing the training of educators (men/women), as well as the artistic experiences developed with teachers (men/women), monitors (men/women) and children of Early Childhood Education. As a result, questions and curiosities arise. But after all, what is the effect of training in arts for Early Childhood Educators (men/women)? What were the pedagogical processes experienced for the construction of the theme on screen? Was there continuity in training and development of artistic activities? We inundated with qualitative research tools, decided to map the entire process: the children's artistic productions, the speech of educators (men/women) and other participants through records made in a Logbook. A semi-structured interview, Discursive Analysis and Documentary Analysis of the material constituting this Forum of Early Childhood Education from South of Minas Gerais also it was tools for collecting the empirical material. All the empirical material collected was duly transcribed and analyzed, together with the documents guiding the actions, aiming mainly to discuss and highlight how the entire production and continuing education process of these professionals (men/women) took place. As a final product, we highlight the creation of a short film with informative intent and highlighting the works and results obtained from the 145th Forum of Early Childhood Education from South of Minas Gerais.